2002
DOI: 10.1161/01.hyp.0000036449.70110.de
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Regulation of Na + -HCO 3 Cotransporter by Angiotensin II Type 1A Receptor

Abstract: Abstract-Although angiotensin (Ang) II is known to regulate renal proximal transport in a biphasic way, the receptor subtype(s) mediating these Ang II effects remained to be established. To clarify this issue, we compared the effects of Ang II in wild-type mice (WT) and Ang II type 1A receptor-deficient mice (AT 1A KO). The Na ϩ -HCO 3 Ϫ cotransporter (NBC) activity, analyzed in isolated nonperfused tubules with a fluorescent probe, was stimulated by 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
65
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 43 publications
(60 reference statements)
6
65
1
1
Order By: Relevance
“…This preparation is suitable for the identification of biphasic effects of Ang II on NBCe1 mediated through basolateral AT 1 receptors. 11,15,17,19 The basal NBCe1 activity (60.062.3 mM/min, n=70) determined from 22 persons ages 59.362.0 years was lower than the activity (82.262.2 mM/min, n=41) from 11 mice ages 9.160.8 weeks. Unlike Ang II in mouse or rabbit PTs, [9][10][11]17 Ang II in human PTs induced a dose-dependent marked stimulation of the NBCe1 activity ( Figure 1A 11,20 The stimulation of NBCe1 by Ang II was largely suppressed by a specific AT 1 inhibitor valsartan ( Figure 1B) and completely suppressed by an mitogen-activated protein kinase/ERK (MEK) inhibitor PD98059 ( Figure 1C), indicating that the AT 1 /MEK/ERK pathway mediates the stimulatory effect of Ang II.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…This preparation is suitable for the identification of biphasic effects of Ang II on NBCe1 mediated through basolateral AT 1 receptors. 11,15,17,19 The basal NBCe1 activity (60.062.3 mM/min, n=70) determined from 22 persons ages 59.362.0 years was lower than the activity (82.262.2 mM/min, n=41) from 11 mice ages 9.160.8 weeks. Unlike Ang II in mouse or rabbit PTs, [9][10][11]17 Ang II in human PTs induced a dose-dependent marked stimulation of the NBCe1 activity ( Figure 1A 11,20 The stimulation of NBCe1 by Ang II was largely suppressed by a specific AT 1 inhibitor valsartan ( Figure 1B) and completely suppressed by an mitogen-activated protein kinase/ERK (MEK) inhibitor PD98059 ( Figure 1C), indicating that the AT 1 /MEK/ERK pathway mediates the stimulatory effect of Ang II.…”
Section: Resultsmentioning
confidence: 96%
“…7,17 Both arachidonic acid and 5,6-EET failed to inhibit the human NBCe1 activity (Supplemental Figure 1), although they did inhibit the mouse NBCe1 activity as reported. 11,17 To further clarify the mechanism(s) underlying the different modes of PT transport regulation by Ang II, we next examined the role of the NO/cGMP pathway, which might also mediate the inhibitory effect of Ang II in the other species. 12,18 As previously reported, 11,17 Ang II had biphasic effects on NBCe1 activity in mouse PTs (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although controversial data have been reported concerning the receptor subtype(s) that are responsible for the biphasic effects of ANG II on proximal tubular transport [87,88], some studies have clearly indicated that both luminal and basolateral AT1A receptors mediate the biphasic effects of Ang II on proximal transport [89][90][91]. It has been shown that at physiological concentrations, binding between ANG II and the AT1 receptor induces the rapid activation of PLC, which results in the release of IP3 and DAG, which are themselves involved in slightly increasing [Ca 2+ ]i by mobilizing Ca 2+ from intracellular storage and by activating PKC, respectively [92][93][94].…”
Section: Dose-dependent Biphasic Effects Of Ang II In the Proximal Tumentioning
confidence: 99%